\begin{gathered}a) \int{(x^4-8x^3+4x)}dx=\\ | \int{x^{\alpha}dx}= \frac{x^{\alpha+1}}{\alpha+1}+C|\\ = \int{x^4}dx-8\int{x^3}dx+4\int{x^1}dx=\\ = \frac{x^{4+1}}{4+1}-8 \frac{x^{3+1}}{3+1}+4 \frac{x^{1+1}}{1+1}+C=\\ = \frac{x^5}{5}- \frac{8x^4}{4}+ \frac{4x^2}{2}+C=\\ = \frac{x^5}{5}-2x^4+2x^2+c;\\ \end{gathered}a)∫(x4−8x3+4x)dx=∣∫xαdx=α+1xα+1+C∣=∫x4dx−8∫x3dx+4∫x1dx==4+1x4+1−83+1x3+1+41+1x1+1+C==5x5−48x4+24x2+C==5x5−2x4+2x2+c;
\begin{gathered}b) \int{\cos(2x)sin(x)}dx=|d(\cos(x))=-\sin(x)dx|=\\ =-\int{\cos(2x)d(\cos(x))}=\\ |\cos(2\alpha)=\cos^2\alpha-\sin^2\alpha=2\cos^2\alpha-1=1-2\sin^2\alpha|\\ =-\int{(2\cos^2(x)-1)}d(\cos(x))=| t=\cos(x)|=\\ =-\int{(2t^2-1)}dt=|\int{x^{alpha}}dx= \frac{x^{\alpha+1}}{\alpha+1}+C|\\ =-2\int{t^2}dt+\int{t^0}dt=-2 \frac{t^{2+1}}{2+1}+ \frac{t^{0+1}}{0+1}=\\ =- \frac{2}{3}t^3+t+C=|t=\cos(x)|=\cos(x)- \frac{2}{3}\cos^3(x)+C=\\ \cos(x)(1- \frac{2}{3}\cos^2(x))+C=\\ =\cos(x)(1- \frac{2}{3}(1-\sin^2(x))+C= \end{gathered}b)∫cos(2x)sin(x)dx=∣d(cos(x))=−sin(x)dx∣==−∫cos(2x)d(cos(x))=∣cos(2α)=cos2α−sin2α=2cos2α−1=1−2sin2α∣=−∫(2cos2(x)−1)d(cos(x))=∣t=cos(x)∣==−∫(2t2−1)dt=∣∫xalphadx=α+1xα+1+C∣=−2∫t2dt+∫t0dt=−22+1t2+1+0+1t0+1==−32t3+t+C=∣t=cos(x)∣=cos(x)−32cos3(x)+C=cos(x)(1−32cos2(x))+C==cos(x)(1−32(1−sin2(x))+C=
\begin{gathered}=\cos(x)(1- \frac{2}{3}+ \frac{2}{3}\sin^2(x))+C=\\ =\cos(x)( \frac{1}{3}+ \frac{2}{3}\sin^2(x))+C=\\ = \frac{1}{3}\cos(x)(1+2\sin^2(x))+C; \end{gathered}=cos(x)(1−32+32sin2(x))+C==cos(x)(31+32sin2(x))+C==31cos(x)(1+2sin2(x))+C;
\begin{gathered}c)\int(e^{3x}+1)dx=\int{e^{3x}}dx+\int{}dx=\\ |\int{e^x}dx=e^x+C; \int{x^\alpha}dx= \frac{x^{\alpha+1}}{\alpha+1}+C;d(x)= \frac{1}{3}dx|}\\ = \frac{1}{3}\int{e^{3x}}d(3x)+\int{x^0}dx=\\ = \frac{1}{3}e^{3x}+ \frac{x^{0+1}}{0+1}+C=\\ = \frac{1}{3}e^{3x}+x+C \end{gathered}
так так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так так
Пошаговое объяснение:
ак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так такак так так так так так так так
для начала нам нудно узнать сколько грибов положили
1)14-10=4 положили грибов
далие нам нужно узнать сколько било сначала
2)85-4=81 било сначала